Influence of a Financial Crisis and the Covid-19 Pandemic on Prices of Cereals in Poland - Krajewski, Łukasz; Witkowska-Dąbrowska, Mirosława; de Jesus, Ilisio Manuel (Olsztyn Economic Journal, 2022)
This article raises the question of the impact of global crises on the grain price market. Prices of wheat, rye, barley, oat and cereal mixture as well as maize were submitted to analysis. The aim of the study was to determine the influence of a financial crisis and the Covid-19 pandemic on prices of cereals in Poland. Two research hypotheses were put forth. The first one assumed that prices of cereals increased due to the 2007-2009 financial crisis. The second research hypothesis was that the Covid-19 pandemic caused fluctuations on the cereal price market. To verify these hypotheses, an analysis was completed using data from the GUS Central Statistical Office (Statistics Poland) In addition, relevant references from the fields of economics and agriculture were reviewed. Based on this study, it has been concluded that both the 2007-2009 financial crisis and the Covid-19 pandemic had significant effects on prices of cereals in Poland.